2021
DOI: 10.3389/fpsyg.2021.642910
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Volunteering Into Treatment for Depression Among Adolescents: Developmental and Clinical Considerations

Abstract: Volunteering, or taking part in unpaid work for the benefit of others, can be a powerful positive experience with returns to both individual well-being and community projects. Volunteering is positively associated with mental health in observational studies with community samples but has not been systematically examined as a potential part of treatment interventions with clinical adolescent samples. In this manuscript, we review the empirical evidence base connecting volunteerism to mental health and well-bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…They suggested that “volunteering can be considered a strategy for successful aging because of its association with health, well-being, and longevity” [ 39 ] (p. 762). Volunteering has also been helpful in the clinical treatment of adolescent depression [ 40 ]. It may be useful to support older adults living with depression (e.g., mild depression) and tackle social isolation among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that “volunteering can be considered a strategy for successful aging because of its association with health, well-being, and longevity” [ 39 ] (p. 762). Volunteering has also been helpful in the clinical treatment of adolescent depression [ 40 ]. It may be useful to support older adults living with depression (e.g., mild depression) and tackle social isolation among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Despite potential motivational and logistical challenges [see Ballard et al (2021)] for a discussion, teens who were referred to our study were very interested in participating. Once enrolled, they were able to find meaningful volunteer opportunities and complete their hours (with the exception of disruptions due to COVID-19).…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacological interventions, such as those based in positive psychology, are desirable to many people either instead of or in conjunction with medication. Based on theoretical and empirical findings detailing positive associations between volunteering and mental health and well-being (Konrath and Brown, 2013;Piliavin and Siegl, 2015;Creaven et al, 2017;Ballard et al, 2021), we believe that volunteering can help young people develop psychosocial assets and reduce symptoms of affective disorders. Importantly, volunteering fits within existing evidenced-based approaches to treating depressive and/or anxiety disorders [see Ballard et al (2021) for full review] and is conceptually consistent with principles of positive psychology interventions, cognitivebehavioral therapy (CBT) and behavioral therapy approaches, including exposure therapy for certain anxiety disorders (Reinecke et al, 1998;Heimberg and Becker, 2002;Butler et al, 2006;David-Ferdon and Kaslow, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…153 Providers can help guide adolescents in strengthening their interpersonal connections. Suggestions can include connections through any of the following: physical activity; participation in clubs or activities for leisure; 154 sports teams; 49,155 faith-based youth organizations; 156 4-H camps; 157 social support groups; volunteer activities; 158,159 or other smaller peer interactions. All of these have been shown to improve psychosocial functioning and reduce depressive symptoms in youth.…”
Section: Social Connectednessmentioning
confidence: 99%